A triptycene-based porous hydrogen-bonded organic framework for guest incorporation with tailored fitting. Issue 26 (7th March 2017) - Yan, Wenqing; Yu, Xiaopeng; Yan, Tao; Wu, Doufeng; Ning, Erlong; Qi, Yi; Han, Ying-Feng; Li, Qiaowei
Abstract : By employing a robust and non-coplanar building block strategy, a triptycene-based hydrogen-bonded organic framework was constructed with almost no sacrifice of molecular surfaces, and it was capable of incorporating C60 molecules in high concentration in the channels with tailored fitting. Abstract : A hydrogen-bonded organic framework (HOF) was constructed by avoiding potential π–π stacking of building blocks with robust and non-coplanar triptycene-based modules. The tailored-fitting interactions were demonstrated by the adsorption of fullerene with a concentration enrichment of ∼420 times in the pores.